Proceedings of the Second Workshop on Fact Extraction and VERification (FEVER) 2019
DOI: 10.18653/v1/d19-6615
|View full text |Cite
|
Sign up to set email alerts
|

FEVER Breaker’s Run of Team NbAuzDrLqg

Abstract: We describe our submission for the Breaker phase of the second Fact Extraction and VERification (FEVER) Shared Task. Our adversarial data can be explained by two perspectives. First, we aimed at testing model's ability to retrieve evidence, when appropriate query terms could not be easily generated from the claim. Second, we test model's ability to precisely understand the implications of the texts, which we expect to be rare in FEVER 1.0 dataset. Overall, we suggested six types of adversarial attacks. The eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…The first two winning systems (Niewinski et al, 2019;Hidey et al, 2020) produce claims requiring multi-hop reasoning, which has been shown to be challenging for fact checking models (Ostrowski et al, 2020). The other remaining system (Kim and Allan, 2019) generates adversarial attacks manually. We instead find universal adversarial attacks that can be applied to most existing inputs while markedly decreasing fact checking performance.…”
Section: Fact Checkingmentioning
confidence: 99%
“…The first two winning systems (Niewinski et al, 2019;Hidey et al, 2020) produce claims requiring multi-hop reasoning, which has been shown to be challenging for fact checking models (Ostrowski et al, 2020). The other remaining system (Kim and Allan, 2019) generates adversarial attacks manually. We instead find universal adversarial attacks that can be applied to most existing inputs while markedly decreasing fact checking performance.…”
Section: Fact Checkingmentioning
confidence: 99%
“…Finally, (Thorne and Vlachos, 2019) provided a baseline for the FEVER 2.0 shared task with entailment-based perturbations. Other participants generated adversarial claims using implicative phrases such as "not clear" (Kim and Allan, 2019) or GPT-2 (Niewinski et al, 2019). In comparison, we present a diverse set of attacks motivated by realistic, challenging categories and further develop models to address those attacks.…”
Section: Related Workmentioning
confidence: 99%
“…Niewinski et al (2019) trained a GPT-2-based model on the FEVER data and manually filtered disfluent claims. Kim and Allan (2019) considered a variety of approaches, the majority of which required understanding area comparisons between different regions or understanding implications (e.g. that "not clear" implies NEI).…”
Section: Adversarial Dataset Evaluationmentioning
confidence: 99%
See 1 more Smart Citation
“…Team NbAuzDrLqg (Kim and Allan, 2019) submitted mostly manually created adversarial claims targeting the retrieval as well as the NLI components of FEVER systems. For the retrieval attacks, the team created claims that didn't contain enti- Table 4: Breakdown of attack type for each breaker and average FEVER scores and Label accuracy for the 8 systems used in the shared task.…”
Section: Breakers Phasementioning
confidence: 99%